2010
DOI: 10.1200/jco.2009.25.3724
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, Randomized, Open-Label Study of Daily Imatinib Mesylate 400 mg Versus 800 mg in Patients With Newly Diagnosed, Previously Untreated Chronic Myeloid Leukemia in Chronic Phase Using Molecular End Points: Tyrosine Kinase Inhibitor Optimization and Selectivity Study

Abstract: A B S T R A C T PurposeTo evaluate the safety and efficacy of initial treatment with imatinib mesylate 800 mg/d (400 mg twice daily) versus 400 mg/d in patients with newly diagnosed chronic myeloid leukemia in chronic phase. Patients and MethodsA total of 476 patients were randomly assigned 2:1 to imatinib 800 mg (n ϭ 319) or 400 mg (n ϭ 157) daily. The primary end point was the major molecular response (MMR) rate at 12 months. ResultsAt 12 months, differences in MMR and complete cytogenetic response (CCyR) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
235
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 261 publications
(248 citation statements)
references
References 23 publications
8
235
1
4
Order By: Relevance
“…Notably, although high‐dose imatinib has been associated with poor tolerability (Cortes et al , 2010; Hehlmann et al , 2011), most patients who had nilotinib dose escalation in this study were able to maintain the higher dose, with 83 of 88 remaining on nilotinib 400 mg twice daily at the end of treatment. Although some of these patients (14 of 88; 15·9%) later discontinued treatment due to suboptimal response or treatment failure, the majority (63·6%) achieved MMR by 24 months.…”
Section: Discussionmentioning
confidence: 72%
“…Notably, although high‐dose imatinib has been associated with poor tolerability (Cortes et al , 2010; Hehlmann et al , 2011), most patients who had nilotinib dose escalation in this study were able to maintain the higher dose, with 83 of 88 remaining on nilotinib 400 mg twice daily at the end of treatment. Although some of these patients (14 of 88; 15·9%) later discontinued treatment due to suboptimal response or treatment failure, the majority (63·6%) achieved MMR by 24 months.…”
Section: Discussionmentioning
confidence: 72%
“…Preliminary results from the study indicated that the CCyR was significantly better at 6 months with HD-IM (45% SD-IM vs 57% HD-IM; P ¼ .0146), but there was no statistical difference in CCyR at 12 months (66% SD-IM vs 70% HD-IM). 51 MMR rates were higher with HD-IM at 3 months and 6 months compared with SD-IM (12% vs 3% at 3 months, P ¼ .0011; 34% vs 17% at 6 months, P ¼ .0002) although no difference in the MMR rate at 12 months was observed (46% vs 40%; P ¼ .20). However, there was a trend toward improved MMR at 12 months in patients who had high Sokal risk scores (26% SD-IM vs 41% HD-IM; P ¼ .16).…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 88%
“…However, there was a trend toward improved MMR at 12 months in patients who had high Sokal risk scores (26% SD-IM vs 41% HD-IM; P ¼ .16). 51 The ELN also performed a randomized study of standard-dose imatinib (400 mg daily) versus high-dose imatinib (800 mg daily) as front-line therapy for patients with high Sokal risk CML-CP in which the CCyR rate at 12 months was the primary endpoint. 52 There was no difference in the CCyR rate at 12 months in the intention-to-treat analysis.…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…At 12 months, there was no statistically significant difference in MMR (46% vs 40%, P ϭ .2035) or CCyR (70% vs 66%, P ϭ .3470), but MMR rates at 3 and 6 months were higher in patients randomly assigned to imatinib 800 mg, as was the CCyR rate at 6 months (57% vs 45%, P ϭ .0146). 12 Longer follow-up is required to determine whether the faster responses achieved with higher doses of imatinib will provide clinical benefit. Nonhematologic and hematologic adverse event rates were higher in the 800-mg arm 12 and, notably, whereas patients assigned to the 400-mg arm achieved an average daily dose of 388.4 mg, patients in the 800-mg arm achieved an average daily dose of only 662.0 mg, indicating the reduced tolerability of higher doses of imatinib.…”
Section: Imatinibmentioning
confidence: 99%